The Skinny on Moisturizers: A Brief Report - Sreeja R. Kuppam (Dermatology, 2020)
Objective To compare the effectiveness of 5 different skin moisturizers using JELL-O® as a model for the human skin. Methods In this study five different moisturizers (Equate®, Burt’s Bees®, Suave®, Aveeno® and Vaseline®) were applied to equivalent samples of JELL-O®. Observations were made over a 12-day period and data was collected at 15 different time intervals. The primary outcome was the height (cm) and weight (g) of the JELL-O® sample at each time interval. The study was an ex vivo experiment conducted in a home laboratory. No Institutional Review Board (IRB) approval was required since the research does not involve living organisms. Results Overall, the JELL-O® sample that had the Vaseline® applied on it had the lowest loss of height and weight. The height stayed at 100% of its original value and the weight only decreased to 97.2% of the original value by the end of the observation period. In contrast, the sample which had Suave® applied to the surface its height and weight decrease the most (42% and 28% respectively). The other moisturizers had effects intermediate between these two extremes. Conclusion Based on this ex vivo head to head study using JELL-O® as a model for the human skin the 5 moisturizers examined had widely differing levels of effectiveness with Vaseline® appearing to be the most protective against evaporative losses and Suave® appearing to be the least.